2014
DOI: 10.1371/journal.pone.0089076
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide Attenuates α-Synuclein Neurotoxicity by an Aggregation-Independent Mechanism in a Rat Model of Familial Parkinson’s Disease

Abstract: The anti-epileptic agent zonisamide (ZNS) has been shown to exert protective effects in neurotoxin-based mouse models of Parkinson disease. However, it is unknown whether ZNS can attenuate toxicity of familial Parkinson’s disease-causing gene products. In this study, we investigated the effects of ZNS on neurodegeneration induced by expression of A53T α-synuclein in the rat substantia nigra using a recombinant adeno-associated virus vector. Expression of A53T α-synuclein yielded severe loss of nigral dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Both of them are pivotal players in DA signaling. A significant negative correlation was found between TH and DAT expression and motor impairment3132. TH and DAT levels were significantly decreased in the brainstem of A53T α-synuclein mice compared with those of the WT littermates, whereas W20, not PBS or ns-scFv, remarkably increased TH and DAT levels in PD transgenic mice (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Both of them are pivotal players in DA signaling. A significant negative correlation was found between TH and DAT expression and motor impairment3132. TH and DAT levels were significantly decreased in the brainstem of A53T α-synuclein mice compared with those of the WT littermates, whereas W20, not PBS or ns-scFv, remarkably increased TH and DAT levels in PD transgenic mice (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…TH is the limiting enzyme in DA synthesis32, whereas DAT is a plasma membrane glycoprotein expressed in DA cells, responsible for DA uptake through a Na + /Cl − coupled cotransport mechanism33. Both of them are pivotal players in DA signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zonisamide has been shown to improve motor function in Parkinson's disease [12]. It is also a candidate drug for disease-modifying therapy because of its protective action on dopamine neurons shown in non-clinical studies [13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…In contrast, others studies showed that oligomers of alpha-synuclein (preaggregates) are more toxic than aggregates (Kaufmann et al, 2016;Lam et al, 2016;Deas et al, 2016;Lorenzen and Otzen 2014). In addition, it has been suggested that aggregate formation is a protective mechanism to prevent cell death (Mahul-Mellier et al, 2015;Arawaka et al, 2014;Danzer and McLean, 2011;Kaganovich et al, 2008).…”
Section: Dopaminergic Degenerationmentioning
confidence: 99%